RADIKALISME DALAM ISLAM - Musthofa Musthofa (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2017)
Radicalism is a movement aimed at creating a change of ideology and social change to its roots. Radicalism is characterized by the emergence of symptoms of change of faith by justification of a certain belief shifted into another belief that resulted in the loss of prior belief. Social change can be known by shifting the values of social behavior into new social values. The approach of research through history to know the emergence of radicalism, indications, factors causing the movement of Islamic radicalism and its implications in life in society. Writing techniques obtained data derived from the literature associated with the subject, and the results of thinking contained in the life of the community. Data collection is documentary. Data analysis is by the description that is data reduction, data presentation, and conclusion. Radicalism in Islam is a movement that contains six elements, namely behavior, goals, goals (direction), material movement, certain places, and opportunities. Indications of radicalism include: (1) response to ongoing conditions in the form of evaluation rejection, (2) rejection of order, (3) have strong belief in an ideology. The cause of Islamic radicalism is the existence of social interactions including socio-political factors, religious emotions, cultural, ideological anti-secularization (secular), and government policy. The implications of radicalism are the emergence of a suggestion that can form a movement with violence, and the succession of the movement of new radicalism in the form of power.